Ber Performance Evaluation Of Ofdm System Using Ldpc-Rs And Ldpc-Cc Product Codes - Chang, Zi Yi (Universiti Sains Malaysia, 2017)
Error control coding techniques is a crucial part of digital communication systems. It is used to solve the errors created by the noise channel during data transmission of digital communication systems. LDPC codes have been shown to offer significant performance gain close to the fundamental limits of channels corrupted by an additive random noise. This thesis particularly investigates the performance of LDPC codes with concatenated Reed-Solomon code (LDPC-RS) and convolutional codes (LDPC-CC) for possible bit-error-rate (BER) performance gain over the Orthogonal Frequency Division Multiplexing (OFDM) system that experiences multipath fading. A channel estimation model for the OFDM system is developed. The OFDM system has an IFFT size of 64. Subsequently, the BER of the signal in OFDM system is examined using Forward Error Correcting (FEC) code namely Convolutional code, Reed-Solomon code, LDPC, LDPC-RS and LDPC-CC. Convolutional code and Reed-Solomon code are implemented using three different code rates which are 1/2, 1/3 and 2/3. The best FEC code with the best BER performance is determined by analysing the SNR versus BER graph. LDPC-CC and LDPC-RS has a performance gain of 6 dB and 5 dB respectively, compared to LDPC at BER of 10−1. It is concluded that concatenated codes (LDPC-CC and LDPC-RS) have better BER performance.